(untitled) (Jurnal Teknologi (Sciences & Engineering), 2018)
Microfiltration membrane made from Sayong ball clay by using uniaxial dry compaction method was used to treat natural organic matter (NOM) source water. A sintering temperature of 900 Â°C to 1000 Â°C were applied. The effect of sintering temperature on membrane porosity, strength and water flux were identified. The porosity of the membrane decreased with increasing sintering temperature and the strength and flux increased with temperature. The membrane was subjected to NOM filtration experiments. The results showed an improvement to the quality of permeate water, where there is a reduction in COD, TSS, BOD5, turbidity, hardness and salinity; and an increased pH value. The effect of chemical cleaning on the fouled membrane also was studied. After cleaning with NaOH solution, a high flux recovery was achieved (up to 50% from the initial pure water flux). The degree of cleanliness of fouled membranes after chemical cleaning was further observed with SEM and EDX analysis.